Legal Due Diligence Dalam Lingkup Hukum Administrasi Negara - Lumbuun, T. Gayus (LAW REVIEW, 2005)
Legal due diligence in the scope of acquiring venture license is an act to find information and fact required to obtain the said license. This writing describes three problems related to due diligence in business license. First, that business license due diligence is an act in its own right in order to form a business venture. On the other hand, however, this kind of due diligence can also be part of a general due diligence that will be used for, among Â other things, merger and acquisition. Second, object of a due diligence for business venture license is prescribed as conditions that have to be met by applicant. This study shows that there is an overlapping and inconsistencies in the said conditions. Third, an applicant of business venture license often faces constraints in his/her endeavor to obtain license. This research is a normative and empirical study with the characteristic of descriptive and explanatory.